Buried in Paperwork: Excessive Reporting in Organizations - Roland Strausz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
This paper offers an explanation why a principal may demand too much paperwork from a subordinate: Due to limited liability and moral hazard a principal is unable to appropriate all rents. Internal paperwork allows a more accurate monitoring of the agent and enables the principal to appropriate a larger part of the agent's rent. In her decision the principal disregards the agent's cost increase of more internal paperwork. Consequently, the requested amount of internal paperwork may be too high from both the agent's personal point of view and the organization as a whole.
urn:nbn:de:bvb:19-epub-13521-3
Keywords: D23; D82; 330